In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.